2014
DOI: 10.1007/s00268-014-2653-5
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Recovery After Surgery Pathway in Patients Undergoing Pancreaticoduodenectomy

Abstract: The ERAS pathway was feasible and safe, yielding an earlier postoperative recovery. An ERAS protocol should be implemented in patients undergoing PD; however, patients with early postoperative low compliance should be carefully managed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
107
0
15

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(131 citation statements)
references
References 33 publications
9
107
0
15
Order By: Relevance
“…16 Braga et al evaluated the compliance to the enhanced recovery protocol and concluded that patients with low compliance had a higher incidence of complications. 40 Our results are in pursuance of previous studies that showed that a CP or standardized care plan for pancreaticoduodenectomy patients resulted in an earlier start of solid enteral feeding and a shorter hospital LOS and less readmissions. Importantly, protocol adherence to predefined targets has not been part of these studies as was analysis of the reasons not following the protocol and its association to outcome.…”
Section: Discussionsupporting
confidence: 61%
“…16 Braga et al evaluated the compliance to the enhanced recovery protocol and concluded that patients with low compliance had a higher incidence of complications. 40 Our results are in pursuance of previous studies that showed that a CP or standardized care plan for pancreaticoduodenectomy patients resulted in an earlier start of solid enteral feeding and a shorter hospital LOS and less readmissions. Importantly, protocol adherence to predefined targets has not been part of these studies as was analysis of the reasons not following the protocol and its association to outcome.…”
Section: Discussionsupporting
confidence: 61%
“…Hence, studies that compared the length of hospitalization between patients operated on after the implementation of the ERAS protocol and patients operated on before its implementation concluded that the period after the start of the protocol entailed a shorter hospitalization and postoperative recovery (9)(10) . A randomized study also concluded that the ERAS protocol mitigates the surgical stress and accelerates the recovery, without increasing the morbidity and mortality rates (11) .…”
Section: The Projects Enhanced Recovery After Surgery (Eras) and The mentioning
confidence: 99%
“…Kim [11] reported that energy intake via oral and intravenous injection approximates to 1,050 kcal/day in a group with postoperative PD patients. Enhanced recovery after surgery study also reported that adherence to postoperative targets was inappropriate: 55% for oral liquids and solid 53% for food [12]. And this study shows that low compliance to regimen was closely related to the severity of postoperative complications [12].…”
Section: Introductionmentioning
confidence: 85%